Deep eutectic solvent-ultrasound assisted extraction as a green approach for enhanced extraction of naringenin from Searsia tripartita and retained their bioactivities - El Maaiden, Ezzouhra; El Kahia, Houda; Nasser, Boubker; Moustaid, Khadija; Qarah, Nagib; Boukcim, Hassan; Hirich, Abdelaziz; Kouisni, Lamfeddal; El Kharrassi, Youssef (Frontiers in Nutrition, 2023)
Naringenin (NA) is a natural flavonoid used in the formulation of a wide range of pharmaceutical, fragrance, and cosmetic products. In this research, NA was extracted from Searsia tripartita using an environmentally friendly, high-efficiency extraction method: an ultrasound-assisted extraction with deep eutectic solvents (UAE-DES). Six natural deep eutectic solvent systems were tested. Choline chloride was used as the hydrogen bond acceptor (HBA), and formic acid, ethylene glycol, lactic acid, urea, glycerol, and citric acid were used as hydrogen bond donors (HBD). Based on the results of single-factor experiments, response surface methodology using a Box-Behnken design was applied to determine the optimal conditions for UAE-DES. According to the results, the optimal NA extraction parameters were as follows: DES-1 consisted of choline chloride (HBA) and formic acid (HBD) in a mole ratio of 2:1, an extraction time of 10 minutes, an extraction temperature of 50 °C, an ultrasonic amplitude of 75 W, and a solid-liquid ratio of 1/60 g/ml. Extracted NA was shown to inhibit the activity of different enzymes in vitro, including α-amylase, acetylcholinesterase, butyrylcholinesterase, tyrosinase, elastase, collagenase, and hyaluronidase. Thus, the UAE-DES technique produced high-efficiency NA extraction while retaining bioactivity, implying broad application potential, and making it worthy of consideration as a high-throughput green extraction method.